Mixture effects on morpho-physiological, grain yield and component traits in upland rice variety mixtures - Meher, J; Das, S R (ORYZA-An International Journal of Rice, 2018)
Rice variety mixture may minimize risk and stabilize production in unfavourable growing conditions for their buffering ability, complementarity, better sharing of resource and space. A study was undertaken to assess the effects of mixture on performance of various morpho-physiological, grain yield and attributing traits by taking six upland rice varieties and their 15 resultant 50:50 bi-varietal mixtures in all combinations. These were grown as monoculture and mixture in two methods of sowing i.e., mixed sowing(MS) and sowing in regularpattern(SRP). Significant mean square value as revealed from analysis of variance for mixture and monoculture for traits like plant height (PH), panicle length (PL), grain number/panicle (GN/P), hundred grain weight(HGW), flag leaf area (FLA) and harvest index (HI) % in MS and SRP. Also mean square was significant for all other traits except EBT/hill in SRP. The mean square for variety showed significant values in all studied traitsexcept GN/P, PN/2-1 m2 and GY/2-1 m2 in MS and EBT/hill in SRP. The mean square values for variety vs mixture were significant for all traits except PL in MS, but were only significant for EBT/hill, HI % and GY/pl. in SRP.Complementation effects (mixture performance better than mean of components monoculture) and over complementation effects (mixture performance better than best component or inferior than poorer component inmonoculture) were estimated for all traits in both the experiments. Complementation effects were significantly positive for GN/P, HGW, FLA and HI%, while negative for PH, PL, PN/2 -1 m2 and GY/2-1 m2 in MS. Likewise, over complementation effects were significantly negative for PH but positive for GN/P and HI% in few mixtures in MS. In SRP, complementation effects were significantly negative for PL, GN/P, HI% and GY/pl. and both positive andnegative for HGW and FLA and almost neutral for PH and EBT/hill. Only in one mixture Annapurna+Suphala complementation was positive for HGW, FLA and GY/pl. In few mixtures over complementation effects were negative wherever exist viz., for traits like GN/P and SF % in Annapurna +Sidhant and for FLA, HI % and GY/pl. in Parijat+ Annada. No significant advantages of mixtures were observed for many traits, although few traits showed some advantage in few mixtures from this study.